Representasi Social Commerce dalam Video Pendek TikTok: Studi Eksploratif Strategi Komunikasi Pemasaran Voucher Makanan pada Konten Affiliator TikTok Go (Studi Kasus Tiga Brand Kategori F&B pada TikTok) - Natasha, Sheila (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The rapid growth of social commerce in Indonesia has been significantly driven by the increasing popularity of TikTok as a short-video platform for promotional purposes. Responding to this trend, TikTok introduced the TikTok Go affiliate program, enabling content creators to act as affiliates by promoting Food & Beverage (F&B) products through personal storytelling and persuasive narratives. This study explores the marketing communication strategies implemented by TikTok Go affiliates in promoting food vouchers. Using a qualitative approach with content analysis, three short TikTok videos from affiliates representing different F&B market segments (KFC economic, Pepper Lunch mid-range, Holycow! premium) were purposively selected based on criteria such as duration under 60 seconds, explicit mention of vouchers, and inclusion of affiliate links. Analysis was conducted using the AIDA (Attention, Interest, Desire, Action) model to examine visual presentation, personal narratives, and call-to-action (CTA) effectiveness. Findings indicate that soft selling combined with authentic storytelling and appealing food visuals effectively engages audiences, particularly in generating interest and driving purchase actions. The use of clear CTAs, integration of Online-to-Offline (O2O) strategies, and adaptation to brand-specific price segments enhanced conversion potential. These results offer practical insights for F&B brands in designing affiliate content that maximizes audience engagement while maintaining narrative authenticity across various market segments.